Utilization of Coconut Water Waste as Liquid Organic Fertilizer for the Growth of Mung Bean Microgreens (Vigna radiata) - Ahmad Ahmad Aldi Nasution; Badrul Ainy Dalimunthe; Khairul Rizal; Yudi Triyanto (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Microgreens represent a novel approach to urban farming, characterized by its simplicity, straightforwardness, and cost-effectiveness. This research aims to evaluate the use of coconut water waste as a liquid organic fertilizer (POC) in promoting the growth of green bean microgreens (Vigna radiata). The study was conducted over one week in the Kotapinang District of South Labuhanbatu Regency, utilizing analysis of variance (ANOVA) to assess four treatments with varying doses of coconut water POC: P0 as the control, 10 ml, 20 ml, and 30 ml. The data collected were analyzed using SPSS version 25.00, and the BNT test was applied at the 5% significance level to evaluate the differences between treatments. The results of the observations indicated that at 4 days after planting (DAP), the P3 treatment yielded the greatest plant height, averaging 13.83 cm. Conversely, at 7 DAP, treatment P1 exhibited the highest growth, with an average plant height of 19.66 cm. In terms of leaf width, treatment P1 also performed the best, with an average leaf width of 1.2 cm. These findings suggest that the application of coconut water as POC can significantly enhance the growth of green bean microgreens.